Possibility of manufacturing particleboard with Acacia salicina - Reza Jazayeri (Regional Information Center for Science and Technology (RICeST), 2008)
In order to survey of possibility of particle board production with «Acacia salicina » the effectiveness of three factor (treatment) included adhesive percentage (in two surface: %9 and %11) temperature degree ( in two surface 1650c and 1750c) pressing time (in three surface: 5/6 and 7 minutes) on mechanical (MOR, MOE, IB) and physical (TS2, TS24) properties were experimented with E.N standard. Therefore 36 boards were prepared for mechanical and physical tests. Data were analyzed with appropriated statistical method. Results indicate %11 adhesive, 1650c temperature degrees and 6 minutes press time is best condition for production. However the results showed more than standard IB (1/24 Mpa ) probably due to its wood chemistry. Therefore this species could be a suitable source to produce particle board